Phenotypical Characterization of Spleen Remodeling in Murine Experimental Visceral Leishmaniasis - Melo, Caroline Vilas Boas de; Hermida, Micely D'El-Rei; Mesquita, Bianca R.; Fontes, Jonathan L. M.; Koning, Jasper J.; Solcà, Manuela da Silva; Benevides, Bruno B.; Mota, Girlândia B. S.; Freitas, Luiz A. R.; Mebius, Reina E.; dos-Santos, Washington L. C. (Frontiers in Immunology, 2020)
Background: Visceral leishmaniasis (VL) is caused by Leishmania infantum or L. donovani infection. One of the main problems related to this disease is the emergence of severe clinical forms with a lethality of 5–20%, even while under specific treatment. In humans and other species susceptible to fatal VL, such as dogs and hamsters, the disruption of splenic white pulp (WP) is accompanied by disease progression. Control of VL progression is seen in BALB/c mice, as evidenced by a mild clinical presentation and controlled parasite replication in the liver and spleen. In this study, we investigated the features involved in the morphological remodeling of splenic compartments associated with the control of VL progression to death. Methods: We evaluated cohorts of BALB/c mice after 30, 60 and 90 days of infection by L. infantum. Spleen morphology, cell population subsets and cytokine production were studied in the spleen using flow- and histo-cytometry. Results: Intraperitoneal infection with 108 promastigotes of L. infantum led to progressive increases in spleen size at 60 and 90 days after infection. Splenomegaly was the only clinical sign of disease observed. At 30 days after infection, hyperplasia in the WP and decreased numbers of plasmacytoid dendritic cells were observed. The WP hyperplasia subsided at 60 days post-infection. However, the splenomegaly remained in association with increased numbers of macrophages, B and T lymphocytes and plasma cells. An increased number of lymphoid tissue inducer (LTi) cells was observed; these were distributed around the periarteriolar lymphoid sheath in control mice and scattered throughout the red pulp in the Leishmania-infected mice. After 90 days of infection, increased IL-6 and IFN-gamma production was seen in the spleen, as well as higher frequencies of follicular and plasmacytoid dendritic cells. Conclusion: The data presented herein emphasizes the potential role of spleen remodeling in the control of severe forms of VL and highlights features potentially involved in this process.